PENGARUH KONDISI KEUANGAN PERUSAHAAN, PEMERIKSAAN PAJAK DAN SIKAP WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK HOTEL - Prayatni, Putu Tia Dewi; Jati, I Ketut (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
Hotel tax is one source of local revenue increasing acceptance. Compliance taxpayers to comply with tax obligations in force plays an important role in the acceptance of tax revenue. This study aims to determine the effect of the company's financial condition, tax audits, and taxpayer attitudes toward tax compliance hotels in Denpasar Revenue Service. The sampling method in this research is done by using accidental sampling technique. Respondents in this study amounted to 100 taxpayer acquired hotel based on the formula Slovin. Data were analyzed using multiple linear regression analysis using SPSS 15:00 for windows. Based on the results of the analysis can be concluded that the company's financial condition variables, examination of tax and taxpayer attitudes positive impact on tax compliance in Denpasar Revenue Service.
Keywords: Financial Condition, tax inspection, the Tax Payer Attitudes, Taxpayer Compliance